2020
DOI: 10.1080/23144599.2020.1765720
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue residue of enrofloxacin in healthy,Eimeria-infected broiler chickens and those pre-treated with amprolium and toltrazuril

Abstract: The pharmacokinetics of enrofloxacin was compared in healthy chickens, Eimeria infected chickens and in Eimeria infected chickens pre-treated with amprolium or toltrazuril following a single IV and oral administration at dose 10 mg/kg. The blood samples were taken after administration at different time intervals (5 min to 24 hours) to determine the pharmacokinetic parameters of enrofloxacin. The different concentrations of enrofloxacin were determined by using HPLC assay method. Serum concentrations versus tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
4
9
0
Order By: Relevance
“…Published data for AUC of 15.2 ± 1.08 µg × h/mL for ENR after i.v. administration at a dose of 10 mg/kg are similar to our findings ( Atef et al, 2020 ). The estimated population pharmacokinetic parameters were in alignment with the published data.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Published data for AUC of 15.2 ± 1.08 µg × h/mL for ENR after i.v. administration at a dose of 10 mg/kg are similar to our findings ( Atef et al, 2020 ). The estimated population pharmacokinetic parameters were in alignment with the published data.…”
Section: Discussionsupporting
confidence: 92%
“…Population values of AUC of ENR were very close to the calculated values by non-compartmental analysis. High bioavailability calculated by population approach is typical for ENR and it was in agreement with the reported values of 77 to 89% in other studies ( Knoll et al, 1999 ; Atef et al, 2020 ). Similar values of C max were found for the main metabolite ciprofloxacin after oral administration of ENR at a dose of 20 mg/kg in broiler chickens ( Xiao et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reported value for the biological half-life of thiamphenicol suggesting that birds pretreated with toltrazuril can slowly remove the drug compared to control chickens. These results agreed with that of Atef et al (2020) who concluded that Eimeria infected birds pre-treated with toltrazuril can eliminate enrofloxacin more slowly compared to control chickens. This difference can be due to the effect of toltrazuril on the removal of drug.…”
Section: Discussionsupporting
confidence: 91%
“…Certainly, the absorption, distribution, metabolism, and excretion characteristics of drugs in animals are necessary studies before they can be applied. The pharmacokinetic studies of toltrazuril in different animals have been gradually revealed, characterized by good oral absorption, long residence time in the body, and significant interspecies differences (5, [20][21][22]. Although toltrazuril is mostly metabolized to ponazuril and excreted through feces, which is similar in chickens, pigs, and rats (5, 6), the kinetics of ponazuril itself in vivo need to be further clarified.…”
Section: Introductionmentioning
confidence: 99%